2022
DOI: 10.1083/jcb.202205051
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear tension controls mitotic entry by regulating cyclin B1 nuclear translocation

Abstract: As cells prepare to divide, they must ensure that enough space is available to assemble the mitotic machinery without perturbing tissue homeostasis. To do so, cells undergo a series of biochemical reactions regulated by cyclin B1-CDK1 that trigger cytoskeletal reorganization and ensure the coordination of cytoplasmic and nuclear events. Along with the biochemical events that control mitotic entry, mechanical forces have recently emerged as important players in cell-cycle regulation. However, the exact link bet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 59 publications
6
23
0
Order By: Relevance
“…S3I; ****p<0.0001) (Appelbaum et al 1990). It has been previously shown that LBR overexpression causes perinuclear ER expansion and the overproduction of nuclear membranes (Ma et al 2007), leading to NE folding and altered nuclear structure (Dantas et al 2022), similar to what we observed in U2-OS and MDA-MB-468 cells. However, interfering with nuclear structure by overexpressing LBR in RPE-1 cells (Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…S3I; ****p<0.0001) (Appelbaum et al 1990). It has been previously shown that LBR overexpression causes perinuclear ER expansion and the overproduction of nuclear membranes (Ma et al 2007), leading to NE folding and altered nuclear structure (Dantas et al 2022), similar to what we observed in U2-OS and MDA-MB-468 cells. However, interfering with nuclear structure by overexpressing LBR in RPE-1 cells (Fig.…”
Section: Resultssupporting
confidence: 89%
“…To do so, we overexpressed an mCherry-tagged version of lamin B receptor (LBR), an integral protein of the inner nuclear membrane (INM) that associates with the nuclear lamina 43 . It has been previously shown that LBR overexpression causes perinuclear ER expansion and the overproduction of nuclear membranes 44 , leading to NE folding and altered nuclear structure 45 , similar to what we observed in U2-OS and MDA-MB-468 cells. However, interfering with nuclear structure by overexpressing LBR in RPE-1 cells (Fig.…”
Section: The Nuclear Lamina Is Not Required For Centrosome Positionin...supporting
confidence: 89%
“…Our dissipative particle dynamics (DPD) model has qualitatively recapitulated the experimental results from living cells that mechanomemory persists in the chromatin, and nucleoplasm diffusivity for tens of minutes after stress cessation and this memory is regulated by the NPCs. Recent reports show that the size of and the transport via the NPCs that is tethered to the cytoskeleton is regulated by the tension in the nuclear envelope ( 21 , 27 ), and transport of RNA via NPCs is unidirectional ( 28 ). Our current finding that the mechanomemory of chromatin diffusivity and nucleoplasm protein diffusivity extends the current understanding of the role of the NPCs and highlights the importance of the molecular exchange between the nucleus and the cytoplasm in regulating external force-induced nuclear activities and functions.…”
Section: Discussionmentioning
confidence: 99%
“…FRET was obtained to assess the heterochromatin condensation state between HP1α-GFP/mCherry and MBD1-EGFP/mCherry ( 40 ). The FRET efficiency (η) was quantified using the following equation ( 27 ): 1 …”
Section: Methodsmentioning
confidence: 99%
“…Several groups identified an alteration of cell mitosis under such confined situations (11,12), with modified cell cycle progression and division (13), the presence of multi-daughter events, daughter cells of unequal size, and induction of cell death (14). Moreover, such flattening was shown to promote the G1-S transition (15), as well as the G2-M transition (16), thus fostering cell cycle progression. Under such confined conditions, the nucleus was highlighted as a mechanosensor (17)(18)(19), triggering a mechanism of nuclear repair (20) and rescue of DNA damage (21).…”
Section: Main Text Introductionmentioning
confidence: 99%